Penguatan Pemahaman Konsep Operasi Bilangan Melalui Pelatihan Intensif Bagi Calon Mahasiswa - Wahyudi; Sumaji; Intan Vidyastari, Rhesma; Amanda Firdaus , Nabilla; Oktavia Sari, Cintia; Eriana, Ananda (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Basic mathematical skills are an important foundation for prospective students’ readiness for higher education; however, in recent years, mastery of integer operations has still needed to be improved and strengthened. This community service activity aimed to enhance prospective students’ understanding and skills in integer operations through intensive training involving the use of artificial intelligence. The implementation method included mapping initial abilities, delivering conceptual material, and conducting guided contextual problem-solving exercises using AI. The activity was carried out in collaboration with students from Muhammadiyah 1 Ponorogo Senior High School as partners in the Community Service (PkM) program. The results showed that the participants’ initial abilities required priority attention and strengthening, with mathematical fact errors being the most dominant. The training had a positive impact in terms of increased conceptual understanding, active participant engagement, and improved cognitive readiness for advanced mathematics learning. This activity contributes as an early intervention and a model for basic mathematics mentoring for prospective students.